Improving the antioxidant status, fat-soluble vitamins, fatty acid composition, and lipid stability in the meat of Grass carp (Ctenopharyngodon idella Val) fed fresh ryegrass (Lolium multiflorum Lam) - Montenegro, Luciano Federico; Descalzo, Adriana Maria; Rizzo, Sergio Anibal; Rossetti, Luciana; Garcia, Pilar Tere; Perez, Carolina Daiana (Elsevier, 2022)
Ctenopharyngodon idella (Grass carp) is one of the most widely produced species in aquaculture. This species is capable of feeding on forage crops and algae. However, few studies have investigated forage feeding in the production of this species. The aim of this work was to evaluate the impact of fresh Lolium multiflorum feeding on the fatty acid and antioxidant fat-soluble vitamin composition, antioxidant status, and lipid stability of C. idella meat. For this purpose, a 120-day feeding trial was conducted. Approximately 300 juvenile C. idella (7.97 ± 0.6 g and 8.82 ± 0.73 cm) were used. Two experimental diets were used: L. multiflorum Lam (annual ryegrass) forage, or pasture diet (PD), and artificial grain diet (GD). Juveniles of C. idella fed PD accumulated a greater concentration of EPA, DPA, and DHA fatty acids after 60 and 120 days (P < 0.05). Conversely, fish fed a grain-based diet accumulated higher omega 6 fatty acid content in their meat. The PD group meat had a higher content of α-tocopherol, lutein, β-carotene, and retinol than the GD group (P < 0.05). The action of these fat-soluble vitamins and micronutrients increased the FRAP and decreased TBARS in the meat of the PD group. These results suggest that L. multiflorum (ryegrass) feeding improves the quality of C. idella meat by increasing the fatty acids beneficial to human health, such as EPA, DPA, and DHA contents. In addition, this diet increases the antioxidant fat-soluble vitamin contents, thus not only improving the nutritional value of the meat but also contributing to lipid stability.